Gastric Sarcina organisms in a patient with cystic fibrosis - Michael A. DiMaio; Walter G. Park; Teri A. Longacre (Elsevier, 2014)
Sarcina are large Gram positive anaerobic bacteria which grow in recognizable tetrads and octets. Less than 10 cases of human infection with Sarcina have been reported, many of these in the setting of delayed gastric transit. Here, we present the first reported case of gastric Sarcina in a patient with cystic fibrosis, a known cause of gastroparesis. Following a 2 week history of intermittent epigastric pain, endoscopic and histologic examination revealed numerous Sarcina organisms in association with linear gastric ulcerations. Yeast forms morphologically compatible with Candida were also identified. The occurrence of Sarcina in cystic fibrosis further confirms the association of this organism with delayed gastric emptying and suggests a possible predisposition in patients with genetic disorders of chloride ion transport, as one previous report occurred in a patient with congenital chloride diarrhea. Recognition of this unique organism in endoscopic biopsies should prompt several diagnostic considerations.